The Level of Comprehension and Reading Speed of the Short Story Duét Maut Among Class XI-1 Students of SMAN 22 Bandung - Ilyas, Erick Muhammad; Nurjanah, Nunuy; Davronbek, Kurbonov (International Journal of Language and Culture, 2025)
The purpose of this study was to determine the relationship between the level of comprehension and reading speed of students, the sample of which was students of SMAN 22 Bandung class XI-I. The data analysis technique was a test technique. Quantitative data analysis techniques were used to analyze the results of the reading comprehension test in the form of average scores. The data analysis procedure was to measure reading speed (KM) and measure reading ability (KMP). Based on the results of the study, it was found that the students' reading speed was 149.05 wpm with a reading comprehension of 59.07. This shows that the students' reading speed is still below the high school criteria of 250 wpm. Students are said to understand the contents of the reading if the level of comprehension reaches 40-60. In line with this statement, students can be said to understand the contents of the reading because they have a level of comprehension of 59.07. Therefore, it can be concluded that students tend to read carefully to better understand the contents of the reading text, which ultimately affects their reading speed to be below standard, while the understanding of the contents meets the student's standards.